Hypostomus khimaera Tencatt, Zawadzki & Fröehlich, 2014 (Siluriformes, Loricariidae) in the upper rio Paraná basin, Brazil: first record and comments on its occurrence - Lopes, Douglas A. [UNESP]; de Souza, Rafael N.; Gomes, Vandergleison C.; Carvalho, Fernando R. [UNESP]; Zawadzki, Claudio H.; Tencatt, Luiz F. C. (Pensoft Publishers, 2024)
Hypostomus khimaera Tencatt, Zawadzki & Fröehlich, 2014 is a species native to the rio Paraguay basin, but it is recorded here from the upper rio Paraná basin for the first time. Our new record was made in the córrego Mimoso, a tributary of the rio Anhanduí, approximately 180 km from the closest previously reported locality. We are unsure whether the occurrence of this species in the upper rio Paraná basin is a consequence of natural phenomena, such as headwater connection during floods or stream capture, or an artificial introduction. Together with the invasive H. cochliodon Kner, 1854, H. khimaera is the second species of the H. cochliodon group recorded in the upper rio Paraná basin. Here, we provide an updated diagnosis of H. khimaera and highlight the differences in opercle exposition as the easiest way to differentiate it from the syntopic and morphologically similar H. cochliodon.
Keywords: Geographic distribution; Hypostomus cochliodon group; rio Anhanduí basin; species distribution; species sharing